2017
DOI: 10.1130/gsatg293a.1
|View full text |Cite
|
Sign up to set email alerts
|

Savor the Cryosphere

Abstract: This article provides concise documentation of the ongoing retreat of glaciers, along with the implications that the ice loss presents, as well as suggestions for geoscience educators to better convey this story to both students and citizens. We present the retreat of glaciers-the loss of ice-as emblematic of the recent, rapid contraction of the cryosphere. Satellites are useful for assessing the loss of ice across regions with the passage of time. Ground-based glaciology, particularly through the study of ice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…We used this method to investigate the microbial communities in ice from two depths in a GS3 ice core and found that significantly different microbial profiles were archived. Unfortunately, glaciers around the world are rapidly shrinking primarily due to the warming of the atmosphere in response to increasing concentrations of greenhouse gases released during the burning of fossil fuels ( Zemp et al, 2015 ; Burkhart et al, 2017 ). This will lead to a gradual loss of the microbial information archived in glacier ice from which past climate and environmental changes may be reconstructed.…”
Section: Discussionmentioning
confidence: 99%
“…We used this method to investigate the microbial communities in ice from two depths in a GS3 ice core and found that significantly different microbial profiles were archived. Unfortunately, glaciers around the world are rapidly shrinking primarily due to the warming of the atmosphere in response to increasing concentrations of greenhouse gases released during the burning of fossil fuels ( Zemp et al, 2015 ; Burkhart et al, 2017 ). This will lead to a gradual loss of the microbial information archived in glacier ice from which past climate and environmental changes may be reconstructed.…”
Section: Discussionmentioning
confidence: 99%
“…To visually establish the factual story of climate change, EIS offers ground-level photographs of extreme ice loss, departing from typical scientific visualizations, such as satellite measurements, computer modelling, and statistics. In doing so, its on-the-ground images can elicit not only a visceral response from viewers but also provoke a sense of immediacy [Burkhart et al, 2017]. In the production of these photographs, EIS inadvertently transforms its visual evidence of climate change into a media form that adheres to and modifies the following principles of transmedia storytelling:…”
Section: Witnessing Climate Change In Action and Telling The Story Ofmentioning
confidence: 99%
“…The rapid mass loss from glaciers has serious environmental consequences for the global sea-level and climate system (Hock et al 2017). The ice loss also affects river systems, which represent the essential habitat for a variety of species and the resource of water for hydroelectric production, irrigation, and municipal water supplies (Burkhart et al 2017). Finally, glaciers have aesthetic, cultural, and recreational value for local inhabitants and tourists (Orlove et al 2008).…”
Section: Introductionmentioning
confidence: 99%